1976
DOI: 10.1017/s0007485300006854
|View full text |Cite
|
Sign up to set email alerts
|

The night resting sites of the tsetse fly Glossina palpalis palpalis (Robineau-Desvoidy) (Diptera, Glossinidae) in northern Nigeria

Abstract: The night resting sites of Glossina palpalis palpalis (R.-D.) were observed in a riverine swamp at Bara, Bauchi Emirate, northern Nigeria. The flies were marked with an ultra violet reflecting paint and released at dusk. They were detected with the aid of an ultra violet light beam. Most of the flies (72%) rest on leaves (50% on the upper sides) and on small twigs and creepers (202%). The average resting height was highest in the mid-rains (3-78 m), dropped in the late rains (2-95 m) and was lowest (1-52 m) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
1
17
0
1
Order By: Relevance
“…gambiensis in selecting sites close to the ground was similar to the results obtained by CHALLIER (1973) and Bois et al (1977) on the same subspecies in Upper Volta. The collection of two males on tree canopies at heights above 3.0 m, shows that some of the flies do occasionally rest at higher levels, as SCHOLTZ et al (1976) found for G.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…gambiensis in selecting sites close to the ground was similar to the results obtained by CHALLIER (1973) and Bois et al (1977) on the same subspecies in Upper Volta. The collection of two males on tree canopies at heights above 3.0 m, shows that some of the flies do occasionally rest at higher levels, as SCHOLTZ et al (1976) found for G.…”
Section: Discussionmentioning
confidence: 52%
“…They concluded that the increased recapture rate during the rainy season was probably because the more equable climate during this period kept flies in the locality, while during the dry season the increasing hostility of the weather caused flies to disperse. This does not seem plausible since the adjoining areas have undergone ruthless clearing (SCHOLTZ et al, 1976) in order to isolate the experimental site and are therefore more inhospitable. The present results indicate that one of the probable reasons for low recapture rates in areas with an abundance of fallen logs may be due to the penetration of released flies through the undergrowth to seek resting sites on fallen logs, where detection is often difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…centralis and G. pallidipes , than for riverine tsetse species, such as G. palpalis and Glossina fuscipes . In both habitats, tsetse often spend nights on or under leaves (Robinson, ; Scholz et al ., ). In riverine systems with thick vegetation, there is perhaps a greater possibility that the vegetation will interfere with the spray reaching its target (Challier, ).…”
Section: Discussionmentioning
confidence: 97%
“…Cependant, dans des conditions locales particulieres, elles sont presque toujours observees ou capturees au repos sur les memes especes de plantes (Laveissiere, 1976 b;Lavaissiere et al, 1979 b;Gruvel, 1975;Turner, 1980 c;Scholtz et al, 1976).…”
Section: Pourquoi Une Telle Etude?unclassified